2020
DOI: 10.1038/s41598-020-67287-w
|View full text |Cite
|
Sign up to set email alerts
|

From extraocular photoreception to pigment movement regulation: a new control mechanism of the lanternshark luminescence

Abstract: the velvet belly lanternshark, Etmopterus spinax, uses counterillumination to disappear in the surrounding blue light of its marine environment. this shark displays hormonally controlled bioluminescence in which melatonin (Mt) and prolactin (pRL) trigger light emission, while α-melanocyte-stimulating hormone (α-MSH) and adrenocorticotropic hormone (ActH) play an inhibitory role. The extraocular encephalopsin (Es-Opn3) was also hypothesized to act as a luminescence regulator. the majority of these compounds (Mt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 123 publications
(157 reference statements)
1
35
0
Order By: Relevance
“…In parallel, this study presents the first analysis of the photophore morphology and coverage in I. brasiliensis (and, more generally, in Dalatiidae). As recently observed in other luminous sharks (Claes and Mallefet, 2009;Claes et al, 2015;Duchatelet et al, 2020b;Mallefet et al, 2021), I. brasiliensis photophores, visible as black dots between placoid scales, are mainly distributed within the ventral epidermis with a clear dorso-ventral gradient. Counterillumination (i.e., ventral light emission that mimic the residual downwelling light in terms of intensity, wavelength and angular distribution to avoid being spotted by underneath swimming predators; Clarke, 1963;Johnsen et al, 2004), as an anti-predatory tool, was suggested to be the bioluminescence function for Dalatiidae species (Widder, 1998.…”
Section: Discussionsupporting
confidence: 77%
“…In parallel, this study presents the first analysis of the photophore morphology and coverage in I. brasiliensis (and, more generally, in Dalatiidae). As recently observed in other luminous sharks (Claes and Mallefet, 2009;Claes et al, 2015;Duchatelet et al, 2020b;Mallefet et al, 2021), I. brasiliensis photophores, visible as black dots between placoid scales, are mainly distributed within the ventral epidermis with a clear dorso-ventral gradient. Counterillumination (i.e., ventral light emission that mimic the residual downwelling light in terms of intensity, wavelength and angular distribution to avoid being spotted by underneath swimming predators; Clarke, 1963;Johnsen et al, 2004), as an anti-predatory tool, was suggested to be the bioluminescence function for Dalatiidae species (Widder, 1998.…”
Section: Discussionsupporting
confidence: 77%
“…For both families, luminescence appears to be dually controlled at the level of (i) the photocyte, site of luminescent reaction, and (ii) the ILS cells, acting as a diaphragm capable of occluding light produced by the photocytes, via melanophore-associated pigment movements (Duchatelet et al, 2020b,d). This was recently demonstrated within ILS cells of the lanternshark, E. spinax (Duchatelet et al, 2020d) i.e., transduction pathways that activate cellular motors such as dynein and kinesin, leading pigment movements within ILS melanophores. The bioluminescence control mechanisms in the two studied etmopterids, as well as in D. licha, might share common features.…”
Section: Luminescence Control Evolutive Conservationmentioning
confidence: 82%
“…The bioluminescence control mechanisms in the two studied etmopterids, as well as in D. licha, might share common features. Moreover, the involvement of extraocular photoreception events in the light emission control of photophores (Duchatelet et al, 2020d), remains to be deciphered for these sharks. Further research are necessary to fully demonstrate the evolutive conservation of luminescence control within etmopterids and dalatiids.…”
Section: Luminescence Control Evolutive Conservationmentioning
confidence: 99%
“…At the photophore top, facing the outside, an iris‐like structure (ILS) made of interspersed pigmented cells surmounted by lens cells is present (6,7). The ILS serves as a photophore shutter via pigment motions (8,9). Etmopteridae luminescence is produced intrinsically even if the luminous system remains to be discovered (10).…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively, in Dalatiidae, luminescence is mainly produced ventrally hence the function seems to be only restricted to counterillumination (11); light emission occurs in photophores presenting a unique photocyte and a less dense or absent ILS (12–14). Up to now, all studied luminous sharks present a singular hormonal control of the light emission (8,9).…”
Section: Introductionmentioning
confidence: 99%